Association between Social Media Exposure to Food and Beverages with Nutrient Intake of Female Adolescents - Adiba, Cholida; Pradigdo, Siti Fatimah; Kartasurya, Martha Irene (UI Scholars Hub, 2020)
Communication technology development has influenced adolescent food choices and intakes. This study aimed to investigate the association between social media exposure to food and beverage content and nutrient intake among female adolescents. The study was conducted in a cross-sectional design. The targeted population was 104 female students aged 14–18 years old at 'XY' High School in Semarang, Central Java, Indonesia. Eighty-one subjects were chosen by clustered random sampling. Data were collected by interviews using structured questionnaires and a 3x24-hour recall method. Data analyses were conducted by chi-square, Fisher exact tests, and logistic regression. The median and standard deviations of social-media, the duration, frequency, and the number of accounts were 2.3±3.00 hours/access, 2.0±2.00 times/day, and 3.6±2.46 accounts/access, respectively. Mean and standard deviations of adequacy levels for energy 107.4±15.39% and protein 124.8±25.8%. Duration of social-media exposures (p-value = 0.040) and body image (p-value= 0.040) were associated with food selection. Food selection was associated with energy (p-value = 0.003) and protein (p-value = 0.002) adequacy levels. After controlling for body image, social-media exposure duration > 2.3 hours had an OR of 3.4 for selecting the accessed foods. It was concluded that social media exposure duration was associated with food selection, which was then associated with energy and protein intakes.